Encicliche. Note storico-teologiche - Charamsa, Krzysztof (Alpha Omega, 2015)
Summary: The article deals with the principal literary genre of Pontifical teaching, the Encyclical Letter. It reflects on its identity and the historical development it has had over the centuries. It concentrates on some characteristic elements of the structure of such magisterial texts, their addressees and questions related to ecclesial and theological reception, with particular attention given to the renewed use of encyclicals in Pontifical magisterium after the Second Vatican Council. Key words: Encyclical Letter, Pontifical Magisterium, the Popes, John Paul II, Benedict XVI, Francis, literary genre. Parole chiave: lettera enciclica, magistero pontificio, Papi, Giovanni Paolo II, Benedetto XVI, Francesco, genere letterario.